Apios chindiana (Fabaceae: Papilionoideae: Phaseoleae), a new species from East China - Wang, Jun-Feng; Jiang, Kai-Wen; Zhong, Jian-Ping; Chen, Yue; Wu, Dong-Hao; Li, Bo-Heng; Pan, Bo; Wan, Kai-Yuan; Chen, Zheng-Hai; Wu, Lian-Hai (Phytotaxa, 2025)
A new species, Apios chindiana K. W. Jiang, J. F. Wang, Z. H. Chen & B. Pan bis, is described and illustrated. This species is currently known only from southern Zhejiang Province and northwestern Fujian Province, China. Phylogenetic analyses based on nuclear ribosomal ITS and chloroplast matK sequences demonstrate that A. chindiana is most closely related to A. fortunei Maxim. However, A. chindiana is readily distinguished from A. fortunei by its membranous-chartaceous leaflets with often shallowly undulate margins and its dull red, bilaterally symmetrical corolla with keel petals that do not twist to one side. Assessments of area of occupancy (AOO) and extent of occurrence (EOO) indicate that Apios chindiana meets the IUCN Red List criteria for Near Threatened (NT). An updated key to Apios species is also provided.